The Success of Implementing Congklak 4.0 Based on RME to Enhance Numeracy Literacy and Mathematical Concept Understanding of Elementary School - Elita Mega Selvia Wijaya; Rudy Setiawan (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This study aims to examine the success of implementing Congklak 4.0, a digital transformation of the traditional Congklak game, as a learning medium based on the Realistic Mathematics Education (RME) approach to improve numeracy literacy and mathematical concept understanding of elementary school students. The research employed a quasi-experimental design involving 62 students from two elementary schools in Malang, Indonesia, divided into experimental and control groups. Data were collected through pretest and posttest instruments on numeracy literacy and conceptual understanding, supported by student response questionnaires. The results showed a significant improvement in the experimental group using Congklak 4.0 compared to the control group, with an average N-Gain of 0.67 (moderate to high category) for numeracy literacy and 0.71 (high category) for conceptual understanding. In addition, 87% of students expressed positive responses to the integration of Congklak 4.0 in mathematics learning, highlighting increased motivation and engagement. These findings indicate that Congklak 4.0 not only preserves cultural heritage by digitalizing a traditional game but also provides an effective, interactive, and enjoyable tool for mathematics learning. The study suggests that integrating digital traditional games with RME can be an innovative strategy to support numeracy literacy improvement programs in elementary schools.